Highly Efficient Cobalt Sulfide Heterostructures Fabricated on Nickel Foam Electrodes for Oxygen Evolution Reaction in Alkaline Water Electrolysis Cells - Ioannis Poimenidis; Nikandra Papakosta; Panagiotis A. Loukakos; George E. Marnellos; Michalis Konsolakis (Surfaces, 2023)
Non-noble metal electrocatalysts for the oxygen evolution reaction (OER) have recently gained particular attention. In the present work, a facile one-step electrodeposition method is applied in situ to synthesize cobalt sulfide nanostructures on nickel foam (NF) electrodes. For the first time, a systematic study is carried out on the impact of the Co/S molar ratio on the structural, morphological, and electrochemical characteristics of Ni-based OER electrodes by employing Co(NO3)2·6 H2O and CH4N2S as Co and S precursors, respectively. The optimum performance was obtained for an equimolar Co:S ratio (1:1), whereas sulfur-rich or Co-rich electrodes resulted in an inferior behavior. In particular, the CoxSy@NF electrode with Co/S (1:1) exhibited the lowest overpotential value at 10 mA cm−2 (0.28 V) and a Tafel slope of 95 mV dec−1, offering, in addition, a high double-layer capacitance (CDL) of 10.7 mF cm−2. Electrochemical impedance spectroscopy (EIS) measurements confirmed the crucial effect of the Co/S ratio on the charge-transfer reaction rate, which is maximized for a Co:S molar ratio of 1:1. Moreover, field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD) and X-ray fluorescence (XRF) were conducted to gain insights into the impact of the Co/S ratio on the structural and morphological characteristics of the electrodes. Notably, the CoxSy@NF electrocatalyst with an equimolar Co:S ratio presented a 3D flower-like nanosheet morphology, offering an increased electrochemically active surface area (ESCA) and improved OER kinetics.